Sound & Vision : Where Technology Becomes Entertainment - AVTech Media Americas Inc. (New York : AVTech Media Americas Inc.)
Sound & Vision is an American magazine covering home theater, audio, video and multimedia consumer products.
Keywords: Multimedia; Technologie